2021
DOI: 10.3390/en14238018
|View full text |Cite
|
Sign up to set email alerts
|

Progress in the Production of Biogas from Maize Silage after Acid-Heat Pretreatment

Abstract: One of the most effective technologies involving the use of lignocellulosic biomass is the production of biofuels, including methane-rich biogas. In order to increase the amount of gas produced, it is necessary to optimize the fermentation process, for example, by substrate pretreatment. The present study aimed to analyze the coupled effects of microwave radiation and the following acids: phosphoric(V) acid (H3PO4), hydrochloric acid (HCl), and sulfuric(VI) acid (H2SO4), on the destruction of a lignocellulosic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Ellenberger [ 46 ] reported that hydrolyzed wood meal represented a viable feedstuff when used for working horses. Nowicka et al [ 47 ] found that acid hydrolysis of maize silage resulted in an increases release of sugar substrates for biogas production, which could be viewed as a surrogate for digestibility. In Experiment 2, while there was an effect of solvent pre-treatment (either acid or alkali) on chemical composition and fermentation, the results do not indicate an improvement in silage quality relative to the untreated control ( Table 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ellenberger [ 46 ] reported that hydrolyzed wood meal represented a viable feedstuff when used for working horses. Nowicka et al [ 47 ] found that acid hydrolysis of maize silage resulted in an increases release of sugar substrates for biogas production, which could be viewed as a surrogate for digestibility. In Experiment 2, while there was an effect of solvent pre-treatment (either acid or alkali) on chemical composition and fermentation, the results do not indicate an improvement in silage quality relative to the untreated control ( Table 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, corn intended for silage production should be harvested earlier, which translates into a lower lignin content in the biomass. Nowicka et al [97] claimed that the lignin content in the corn silage they tested was 2.6% d.w., while the content of polysaccharides, which after hydrolysis can be processed by microorganisms, was 20.1% and 14.6% d.w. in the case of cellulose and hemicellulose, respectively. Considering the data given in Table 2, it can be stated that cellulose dominates in crude fiber fraction, reaching up to 50% d.w., while the content of lignin in CCC biomass is usually lower than 10% d.w. Late harvest usually leads to an increase in the lignin content in CCC biomass, causing a decrease in biodegradability.…”
Section: Features Of CCC Biomass Important Because Of Biochemical Con...mentioning
confidence: 99%
“…For a fixed duration of pretreatment time, methane production of JAS showed an upward trend with higher HCl concentration and temperature at first, yet gradually decreased (Figure 2 (b)). The higher acid concentration caused a successive decrease in methane production, which could be attributable to the inhibitory effect on the formation of phenolic compounds, furfural, and 5-hydroxymethyl furfural (Nowicka et al 2021). Meanwhile, Günerhan et al (2020) investigated the optimization of pretreatment processes of fruit and vegetable harvesting wastes, revealing that a higher HCl concentration would decrease the concentration of soluble sugars that can be converted directly into methane.…”
Section: Optimization Of Operating Parameters For Methane Productionmentioning
confidence: 99%